A qualitative study on gendered barriers to livestock vaccine uptake in Kenya and Uganda and their implications on Rift Valley fever control - Mutua, Edna N.; Haan, Nicoline C. de; Tumusiime, Dan; Jost, Christine; Bett, Bernard K. (MDPI, 2019)
Rift Valley fever (RVF) is a zoonotic disease of great public health and economic importance transmitted by mosquitoes. The main method of preventing the disease is vaccination of susceptible livestock before outbreaks occur. Studies on RVF vaccines have focused on the production processes, safety, and efficacy standards but those on uptake and adoption levels are rare. This study sought to understand the barriers faced by men and women farmers in the uptake of livestock vaccines to inform strategies for optimizing the use of vaccines against RVF in East Africa. The cross-sectional qualitative study utilized the pairwise ranking technique in sex disaggregated focus group discussions to identify and rank these barriers. Results indicate that men and women farmers experience barriers to vaccine uptake differentially. The barriers include the direct and indirect cost of vaccines, distances to vaccination points, availability of vaccination crushes, intra-household decision making processes and availability of information on vaccination campaigns. The study concludes that vaccine provision does not guarantee uptake at the community level. Hence, these barriers should be considered while designing vaccination strategies to enhance community uptake because vaccine uptake is a complex process which requires buy-in from men and women farmers, veterinary departments, county/district and national governments, and vaccine producers.